BS 7211 AMD1. Electric cables. Thermosetting insulated and thermoplastic sheathed cables for voltages up to and including 450/750V for electric power and lighting and having low emission of smoke and corrosive gases when affected by fire. (16th June 2020) - British Standards Institution,
No abstract available